The Effect of Resistance Training on Malondialdehyde and Protein Carbonyl Concentration in the Heart Tissue of Rats Exposed to Stanozolol - Ayat Arjmand; Bahram Abedi; Ali Hosseini (Pharmaceutical and Biomedical Research, 2020)
Background: Consumption of anabolic steroids causes damage to various tissues, including the heart. Objectives: This study aimed to investigate the effect of Resistance Training (RT) on Malondialdehyde (MDA) and Protein Carbonyl (PC) in the heart tissue of rats exposed to stanozolol (S). Methods: In this experimental study, 18 rats with the mean age of 8 weeks and weight range of 150 to 200 g were selected and divided into three groups of 6 rats: 1. Sham (normal saline consumption) (Sh), 2. S, and 3. S+RT. For 8 weeks, the S and S+RT groups received 5 mg/kg/d S, and the S+RT group performed 5 RT sessions per week. Measurement of MDA and PC in the heart tissue was performed with the enzyme-linked immunosorbent assay. Results: Stanozolol had a significant effect on increasing MAD (P=0.001) and PC (P=0.03) in the heart tissue. However, RT led to a decrease in MDA and PC in the heart tissue of rats exposed to S (P=0.001). Conclusion: It appears that S consumption leads to an increase in MDA and PC levels in the heart tissue, while RT can improve the elevated levels of MDA and PC.